PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN APRESIASI SENI RUPA SISWA KELAS III SD NEGERI 145 PEKANBARU - Lilisniati Arlis; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac: The problem in this research is in art appreciation learning students'appreciation level is still very low, there are still many children who do not recognizethe symbols and motifs own region. Very obvious from the problems of the students, howthe child to perform the process and eventually gave birth to the attitude in scrut inizingthe art. So that students feel learning SBK become stedious, as a result students can notabsorb the information properly. Among them are applying the learning model moreattractive to the environmental conditions of students in everyday life. Direct LearningModel provides an opportunity for students tolearn with a pleasant atmosphere, involvestudents consciously or unconsciously that can improve the ability of art appreciationthird grade students of SD Negeri 145 Pekanbaru. Subjects in this study were studentsof class IIIB Elementary School 145 Pekanbaru academic year 2014/2015 the numberof students 32 people. This research was conducted in two cycles with two daily testsand. Data collection instruments in this study was the observation sheet student, teacherobservation the testend of the cycle. Data collection instruments in this study was theobservation sheet student, teacher observation sheet and repeat the testend of the cycle.The study is in the form of classroom action research (PTK), this study aims to improvethe Appreciation of Fine Arts Elementary School third grade students Pekanbaru on thematerial symbol on the three dimensional art works. These results in dicate that thedirect learning model can improve students ability of art appreciation. The ability ofthestudent's appreciation of art can be seen from the increase in base score with anaverage of 39.53 with the category of not being able, first cycle with an average of64.68 with acapable categories and the second cycle ofthe average value of74.84 bycategory capable. Evident from the average score of the base, the first cycleand secondcycle increase occurred in the first cycle of 63.62% and experienced avery significantincrease seen in the second cycle of 89.32%. Results obtained data refer to the standardof ability appreciation of art, and this means that Direct learning model can improvestudents'art appreciation class III State 145 Pekanbaru.Keywords: Direct Learning Model, ArtsAppreciation2